Luminal narrowing of coronary capillaries in human hypertrophic hearts: an ultrastructural morphometrical study using endomyocardial biopsy specimens. Issue 1 (1st January 1998) - Takemura, G; Takatsu, Y; Fujiwara, H
Abstract : Background: Abnormal microcirculation has been suggested in hearts with pathological conditions, particularly in hypertrophic hearts, even in the presence of normal epicardial coronary arteries. However, the morphology of coronary capillaries has not been well investigated in those hearts. Methods: Ultrastructural morphometry of the capillaries in 47 endomyocardial biopsy specimens taken from 30 patients was performed. Patients: Six patients had hypertrophic cardiomyopathy with dilated cardiomyopathy-like features (DCM-like HCM), six had HCM, six had DCM, five had postmyocarditis, and seven were normal subjects. Results: The short axial diameters of capillaries were similar among the groups. Abnormal stenosis of more than 90% luminal narrowing was found in 31% of capillaries of the DCM-like HCM group, 16% of the HCM group, 13% of the DCM group, 11% of the postmyocarditis group, and 2% of the normal subjects. Mean (SD) stenosis of the lumen was most severe in DCM-like HCM (78(8)%), and more severe in HCM (67(9)%), DCM (66(8)%), and postmyocarditis (68(4)%) than normal subjects (56(8)%). The mean cross sectional areas of capillaries were similar among the groups; however, the endothelial cellular area was significantly (p < 0.05) greater in DCM-like HCM (24.2 (8.2) μm 2 ) than in normal subjects (14.7 (1.8) μm 2 ), indicating that capillary narrowing was due to the increased volume of capillary endothelial cells. The endothelial cells of the stenosed capillaries showed severely oedematous changes of the cytoplasm wholely or partially, but the cytoplasmic organelles and nuclei appeared intact. Conclusion: Narrowing of the coronary capillaries may be of pathophysiological significance in microcirculatory abnormality in hypertrophic hearts, particularly in patients with DCM-like HCM.